THU0306 ROLE OF 18-FDG PET/CT IN DIAGNOSIS AND FOLLOW UP OF LARGE VESSELS VASCULITIS. (2nd June 2020) - Gigante, L.; Bruno, D.; Feudo, V.; Bosello, S. L.; Leccisotti, L.; Musto, A.; Cerasuolo, P. G.; Zoli, A.; Giordano, A.; Gremese, E.
Abstract : Background: 18-FDG PET/CT is a functional imaging method which allows to identify inflammation of vessel walls. The use of PET in large vessels vasculitis(LVV) at disease onset and during follow up is still debate either to confirm clinical remission either to drive the therapy choice. American Society of Nuclear Cardiology (ASNC) recently advanced recommendations aimed to standardize the application of PET in LVV(1). Objectives: The aim of our study was to assess the clinical role of PET performed in patients affected by LVV at the diagnosis and during the follow up. Methods: We retrospectively evaluated PET/CT of 49 patients affected by clinically active LVV according to LVV visual grading (LVG, grading 0-3) and measured the standardized uptake value(SUV) of large vessels. 38 (77, 6%) patients were affected by Giant Cells Arteritis and 11(22, 4%) by Takayasu Arteritis. 32(65.3%) patients repeated the imaging after a mean follow-up of 11.5±5.4 months. All baseline (T0) and follow up (T1) clinical data of disease activity were collected. Patients were treated according to EULAR LVV management recommendations(2). T0 PET/CT study was performed in patients with a clinically active disease defined by suggestive symptoms/signs and/or high inflammatory markers. The mean disease duration before T1 PET/CT examination was 4 months. T0 PET was performed in 25/49 patients(52%) at the diagnosis of LVV, whereas in 24/49(48%) patients with already diagnosed but active LVV disease. Results: Baseline PET was positive in 21 patients(42.9%). According to ASNC recommendations, 19 patients (38.8%) presented a LVG=3, 2(4.0%) a LVG=2, 6(12.2%) LVG=1 and 22 (44.9%) LVG=0. Patients performing PET at disease onset(75%) had higher LVG score than patients performing PET during the disease course (25%), p=0, 002. At T0, aortic, carotid, axillary and subclavian SUV did not correlate with inflammatory markers. Follow up PET/CT studies were performed in 32 patients, 13 (40.6%) with a clinically active disease despite therapy, while 19(59.4%) in clinical remission. Follow up PET was still positive in 8 patients (25%) with a LVG=3, 10 (31.2%) patients presented LVG=1 and 14 (43.8%) LVG=0. T1 PET/CT study showed a significant reduction of SUV values in descending aorta, left and right subclavian arteries, and left and right axillary arteries when compared with first PET/CT study. According to LVG, 12 patients with active PET/CT study at T0 (19 pts) presented a reduction of LVG from score 2 and 3 to grade 1 or 0 (64.2%) at second PET/CT study. Only 3 patients presented an increased LVG score at T1, while in the other 17 patients T1 PET confirmed the previous score. No significant difference was found between LVG scores according with clinical characteristics, but among 8 patients presenting an active T1 PET, 4(50%) were in clinical remission. Conclusion: The use of ASNC recommendations for FDG PET/CT in LVV enables to confirm a metabolically active disease in 40% of patients and in 75% of patients at disease onset, suggesting that post-posing the exam could lead to underrate the real extension of disease. Our data, even if limited, suggest that PET/CT could be crucial in management of patients in clinical remission, detecting patients with still metabolically active LVV. Further prospective studies are necessary to evaluate the role of PET/CT in driving therapeutic strategies. References: [1]Slart R et all - Eur J Nucl Med Mol Imaging, 2018 [2]Hellmich et all – Ann Rheum Dis 2018 Disclosure of Interests: Laura Gigante: None declared, Dario Bruno: None declared, Vanessa Feudo: None declared, Silvia Laura Bosello Speakers bureau: Abbvie, Pfizer, Boehringer, Lucia Leccisotti: None declared, Alessia Musto: None declared, Pier Giacomo Cerasuolo: None declared, Angelo Zoli: None declared, Alessandro Giordano: None declared, Elisa Gremese Speakers bureau: Abbvie, BMS, Celgene, Jannsen, Lilly, MSD, Novartis, Pfizer, Sandoz, UCB